2022
DOI: 10.3390/ijms23116115
|View full text |Cite
|
Sign up to set email alerts
|

Thirty Years’ History since the Discovery of Pax6: From Central Nervous System Development to Neurodevelopmental Disorders

Abstract: Pax6 is a sequence-specific DNA binding transcription factor that positively and negatively regulates transcription and is expressed in multiple cell types in the developing and adult central nervous system (CNS). As indicated by the morphological and functional abnormalities in spontaneous Pax6 mutant rodents, Pax6 plays pivotal roles in various biological processes in the CNS. At the initial stage of CNS development, Pax6 is responsible for brain patterning along the anteroposterior and dorsoventral axes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 174 publications
0
21
0
Order By: Relevance
“…Paired box gene (PAX6) refers to a sequence‐specific DNA‐binding transcription factor, positively and negatively regulating transcription 18 . A previous study has indicated that miR‐129‐5p directly targets the 3′‐untranslated region (UTR) of PAX6 19 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paired box gene (PAX6) refers to a sequence‐specific DNA‐binding transcription factor, positively and negatively regulating transcription 18 . A previous study has indicated that miR‐129‐5p directly targets the 3′‐untranslated region (UTR) of PAX6 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Paired box gene (PAX6) refers to a sequence-specific DNA-binding transcription factor, positively and negatively regulating transcription. 18 A previous study has indicated that miR-129-5p directly targets the 3′-untranslated region (UTR) of PAX6. 19 It is also reported that PAX6 is increased in non-small-cell lung cancer (NSCLC) and directly inhibited by miR-129-5p.…”
Section: Introductionmentioning
confidence: 99%
“…Mutations in PLOD1 or PLOD2 are linked with Ehlers-Danlos syndrome type VI in patients [32] , who present ocular similarities to Axenfeld-Rieger anomaly/Axenfeld-Rieger syndrome, particularly glaucoma and microcornea [10,33] . PAX6 gene is reported to influence development of the central nervous system and also has been known as a key regulator of eye development [34] . Pathogenic mutations of PAX6 also have been demonstrated to involve in the congenital cataracts, aniridia, anophthalmia and other multiple ocular defects in human [35] .…”
Section: Expression Of Plod2 Plod1 Pax6 Col4a2 and Tgf-β In Hle-b3mentioning
confidence: 99%
“…Previous studies showed that congenital aniridia (lack of an iris) in humans and murine small eye phenotypes, both arise from homologous defects in Pax6 [56,57]. In mice, the heterozygous Pax6 phenotype is associated with small eye, while Pax6 homozygous mutant mice lack eyes and a nose and die after birth [58]. Pax6 is expressed in the lens, corneal epithelium, retinal neuroepithelium, and olfactory placodes/epithelium [59][60][61][62].…”
Section: Plos Pathogensmentioning
confidence: 99%